Resolution of 9,10-Diketo[7]helicene and Its Use in One-Step Preparation of Helicene-Based D-A-D Push-Pull Systems - Kos, Martin; Beránek, Tomáš; Císařová, Ivana; Cuřínová, Petra; Žádný, Jaroslav; Storch, Jan; Církva, Vladimír; Jakubec, Martin (The Journal of organic chemistry, 2024)
Racemic 9,10-diketo[7]helicene was successfully separated into enantiomers using a reversible and stereoselective reaction with 2,2'-diamino-1,1'-binaphthalene with moderate yields but with remarkable purity (>99% de). The enantiomerically pure diketone was used as a convenient starting material for the preparation of helicene-based push-pull molecules, which incorporated aza-aryl acceptors and diarylaminophenylene donor groups in a single step. A series of six push-pull systems, along with three reference molecules without donors, were prepared and studied using UV/vis and fluorescence measurements, circular dichroism, and DFT calculations.